2021
DOI: 10.3390/app11083297
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Personal Innovativeness and Users Experience in Accepting the Smart Meter Technology

Abstract: The rapid development of smart technologies and data analytics empowers most industries to evolve their systems and introduce innovative applications. Consequently, smart metering technology, an internet of things-based application service, is diffusing rapidly in the energy sector. Regardless of its associated benefits, smart meters continue to struggle from consumers’ acceptance. To promote smart meters’ successful deployment, research is needed to better understand consumers’ acceptance of smart metering. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 66 publications
2
35
0
Order By: Relevance
“…Symbolic innovativeness specifies the implication of symbolic aspects of the vehicle for the users (Schuitema et al, 2013;Morton et al, 2016). PI has bees theorized to have a moderation effect (Alkawsi et al, 2021;Cheng, 2014). According to the discussion above the sixth hypothesis is generated: H6.…”
Section: Moderating Effects Of Personal Innovativenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Symbolic innovativeness specifies the implication of symbolic aspects of the vehicle for the users (Schuitema et al, 2013;Morton et al, 2016). PI has bees theorized to have a moderation effect (Alkawsi et al, 2021;Cheng, 2014). According to the discussion above the sixth hypothesis is generated: H6.…”
Section: Moderating Effects Of Personal Innovativenessmentioning
confidence: 99%
“…An individual with high innovativeness makes their decisions to buy or use a new technology regardless of others' opinion or experience (Jianlin and Qi, 2010). Personal innovativeness is argued to have a moderation impact on links among factors motivating behavioral intention (Alkawsi et al, 2021).…”
Section: Moderating Effects Of Personal Innovativenessmentioning
confidence: 99%
“…Individuals are dissimilar in their tendency to follow novel regulations [14]. Generally, innovation diffusion investigations identified that highly innovative individuals are active information explorers.…”
Section: Personal Innovativeness and Citizens' Readiness To Follow Co...mentioning
confidence: 99%
“…To better cope with citizens' readiness to follow COVID-19 preventive measures, it is also essential to consider the peer referent and personal innovativeness issues as literature explored opinions of friends and family members influenced an individual's intention to accept a new system [11,12]. Additionally, the better innovativeness of an individual develops a more positive acceptance behavior [13,14]. However, the findings reported in these investigations are still inconsistent and indecisive.…”
Section: Introductionmentioning
confidence: 99%
“…Alkawsi et al [40] studied an acceptance model to evaluate user experience and innovation factors for application with residential consumers. Yang et al [41] investigated the cost-effective design and privacy control of SMs in energy systems using rechargeable batteries.…”
Section: Related Workmentioning
confidence: 99%